Pesticide residues in food : report 2003. - Report of the joint meeting of the FAO panel of experts on pesticide residues in food and the environment and the WHO core assessment group on pesticide residues, Geneva, Switzerland, 15th-24th september, 2003; World Food Organization; Food and Agriculture Organization of the United Nations (Rome : World Health Organisation, 2004)
Proceedings and papers of a workshop; in the Indian context.
Includes bibliographical references.
Keywords: Pesticide residues in food